Capillary-driven coalescence of bidisperse particle rafts with tunable cohesion - Burns, Cameron (My University, 2024)
When objects float on a liquid interface, they deform the surface under their weight. Nearby floating objects naturally clump together to minimize the energetically expensive deformation of the liquid surface through the so-called ‘Cheerios effect,’ a consequence of capillary forces. If many particles are placed on a liquid surface they aggregate to form a particle raft, and when two particle rafts meet they can merge and form a larger structure in a manner similar to the coalescence of liquid droplets. In this thesis, we present an experiment to study the physics of particle raft coalescence using a system of microscopic, cohesive oil droplets. A bidisperse collection of oil droplets is created in a chamber filled with an aqueous solution of sodium dodecyl sulfate, a surfactant which both stabilizes the droplets and introduces a short-range attractive force. The aggregate of droplets is manually separated into two nearly circular rafts then released. The process is directly observed with a camera from above as capillary forces drive the rafts to coalesce. Modifying the cohesion through the concentration of surfactant, we observe that greater cohesion impedes the progression of coalescence such that the structure ceases evolution in a more extended shape. We discuss the spatial distribution of particle rearrangements and develop a simple theory which captures the time evolution of the coalescing rafts.
Coalescence of cohesive particle rafts